STORYTELLING METHOD TO IMPROVE STUDENT’S VOCABULARY IN RA SEMBILAN BINTANG CITAYAM - rr.astri indriana octavita; Rima Novia Ulfa (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2020)
Vocabulary is an important component in teaching English in addition to other components such as structure, pronunciation and intonation. Vocabulary has a very vital role. If a student is weak in the habit of using vocabulary, then the student cannot communicate his thoughts and ideas as accurately as he wants both oral and written. The method of storytelling is a method for developing children's language skills, while the function of storytelling is to help the development of children's language skills, by adding vocabulary vocabulary, saying words, training in composing sentences in accordance with the stage of development.The method of storytelling is a one of method to develop children's language skills, while the function of storytelling is to help the development of students' language skills, by adding vocabulary vocabulary, saying words, training in composing sentences in accordance with the stage of development. The method of storytelling was chosen by the researchers to demonstrate it infront of RA Sembilan Bintang students, which is locatd in Citayam, West Java.